Different scalabilities of N- and P-Type tunnel field-effect transistors with Si/SiGe heterojunctions - Nguyễn, Đăng Chiến (IEEE Publishing, 2024)
The dimensional scaling of tunnel field-effect transistors (TFETs) is an indispensable issue to make them competitive with traditional metal-oxide-semiconductor field-effect transistors (MOSFETs). This paper elucidates the scalabilities of very potential TFETs utilizing Si/SiGe heterojunctions operated in n- and p-type operation modes. Although using the Si/SiGe heterostructures helps to improve the on-currents of both n- and p-type TFETs, its assistance in scaling the device dimension is essentially different between the n- and p-type modes. The asymmetric band-offset of Si/SiGe heterojunctions associated with the asymmetric properties of tunneling in n- and p-type TFETs are responsible for the scalability difference. With a high scalability down to sub-10 nm, the graded Si/SiGe heterojunction p-type TFET exhibits a feasible candidate for low-power and highly-scaled integrated circuits.